Cardiac arrhythmias and amyloidosis - Salinas-Arce, Jorge (2022)
Cardiac amyloidosis (CA) is a form of cardiomyopathy characterized by the extracellular deposit of protein fibers in the myocardium, leading to the development of heart failure, arrhythmias, and electrical conduction system alterations. It is known that most cardiomyopathies have a close relationship with heart rhythm abnormalities, however, CA is specially related to different kinds of arrhythmias even in pre-diagnosis stages. Arrhythmias like atrial fibrillation are present in up to 70% of patients with CA associated with a high risk of cardioembolic complications independent of the risk stratification. Ventricular arrhythmias are frequent, but the use of implantable cardioverter defibrillator has not been demonstrated to improve survival. The Atrial-Ventricular node disease is also common, and is frequently associated with the implantation of a pacemaker, even in asymptomatic patients. In this review, we clarify the recommendations of the most current guidelines, summarize historical and contemporaneous data and describe evidence-based strategies for the management of arrhythmias and their complications in CA.